2021
DOI: 10.1039/d0ra10115j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of H2SO4/H2O2 pre-treatment on electrochemical properties of exfoliated graphite prepared by an electro-exfoliation method

Abstract: Early expansion of graphite after H2SO4/H2O2 pre-treatment and cyclic voltammograms of exfoliated graphite (EG) prepared with various volume fractions of H2O2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…These results show that the specific EG capacitance increased as a higher ultrasonication power was applied during synthesis, owing to the higher surface area. A higher surface area generates a larger electroactive area to store the ions, which caused an increasing electrode capacitance. , However, EG 720 has a lower specific capacitance than EG 480 due to its lower surface area, as determined from the BET measurement. The rate capability of the prepared electrodes was measured at various current densities, and the results are depicted in Figure S5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results show that the specific EG capacitance increased as a higher ultrasonication power was applied during synthesis, owing to the higher surface area. A higher surface area generates a larger electroactive area to store the ions, which caused an increasing electrode capacitance. , However, EG 720 has a lower specific capacitance than EG 480 due to its lower surface area, as determined from the BET measurement. The rate capability of the prepared electrodes was measured at various current densities, and the results are depicted in Figure S5.…”
Section: Resultsmentioning
confidence: 99%
“…Before the electrochemical exfoliation process, graphite sheet as the precursor was dipped in the H 2 SO 4 / H 2 O 2 mixture for 3 min at ∼25 °C following the procedure in our previous work. 12 The solution was made by mixing 38 mL of concentrated H 2 SO 4 (96 wt %) and 2 mL of H 2 O 2 (50 wt %) for 5 min to obtain the H 2 SO 4 /H 2 O 2 mixture with a mole ratio of 95:5. After 5 min, the dipped graphite sheet was lifted from the H 2 SO 4 / H 2 O 2 mixture and let hang for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicated that FeS 2 had better conductivity or electron mobility in the sample after 3 wt% PVP addition. 61,62 The R ct value increased due to the higher dead mass that was wrapped around the active material sites, increasing the resistance at high PVP concentration.…”
Section: Role Of Pvp On the Fes 2 /Pvp Supercapacitormentioning
confidence: 99%